Peroxisome and pexophagy in neurological diseases - Weilin Xu; Jun Yan; Anwen Shao; Cameron Lenahan; Liansheng Gao; Haijian Wu; Jingwei Zheng; Jianmin Zhang; John H. Zhang (Fundamental Research, 2024)
Peroxisomes and pexophagy have gained increasing attention in their role within the central nervous system (CNS) in recent years. In this review, we comprehensively discussed the physiological and pathological mechanisms of peroxisomes and pexophagy in neurological diseases. Peroxisomes communicate with mitochondria, endoplasmic reticulum, and lipid bodies. Their types, sizes, and shapes vary in different regions of the brain. Moreover, peroxisomes play an important role in oxidative homeostasis, lipid synthesis, and degradation in the CNS, whereas its dysfunction causes various neurological diseases. Therefore, selective removal of dysfunctional or superfluous peroxisomes (pexophagy) provides neuroprotective effects, which indicate a promising therapeutic target. However, pexophagy largely remains unexplored in neurological disorders. More studies are needed to explore the pexophagy's crosstalk mechanisms in neurological pathology.